Oxiracetam Offers Neuroprotection by Reducing Amyloid β-Induced Microglial Activation and Inflammation in Alzheimer's Disease - Zhang, Heng; Jia, Longfei; Jia, Jianping (Frontiers in Neurology, 2020)
Abstract Background: Alzheimer’s disease (AD) is characterized by amyloid beta (Aβ) accumulation in the brain, which triggers the activation of microglia; in turn, microglia release neuroinflammatory factors capable of damaging neurons. Thus, a therapeutic approach targeting this sustained microglia-induced inflammatory response deserves investigation. Here, we examined whether oxiracetam (ORC), a nootropic of the racetam family, can indirectly prevent Aβ-induced neurotoxicity by attenuating microglial activation. Methods: Aβ42 oligomers were used to stimulate BV2 microglial cells, and the morphological changes and phagocytic capacity of BV2 cells was evaluated using fluorescence microscopy. We used quantitative reverse transcription polymerase chain reaction to assess the inhibitory effects of ORC on Aβ-induced mRNA levels of interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α); enzyme-linked immunosorbent assay was used to examine the productions of these cytokines. We also assessed the mRNA level of inducible nitric oxide synthase and the production of nitric oxide (NO). The conditioned medium from BV2 cells was used to culture hippocampal HT22 cells to assess indirect toxicity using the MTT assay. Results: ORC prevented the Aβ-induced activation of BV2 cells, as reflected by reduced morphological changes and phagocytic ability. In addition, ORC downregulated the expression of Aβ-induced cytokines (IL-1β, IL-6, and TNF-α) and the production of NO in BV2 cells. Furthermore, ORC protected HT22 cells from indirect damage evoked by Aβ-treated BV2 cell-conditioned medium, but not from direct Aβ-induced toxicity. Conclusions: ORC suppressed the activation of BV2 cells, decreased the production of Aβ-induced inflammatory molecules and NO in BV2 cells, and protected HT22 cells against indirect toxicity mediated by Aβ-treated BV2 cell-conditioned medium. Thus, ORC may exert a protective role in AD through attenuating the damage caused by inflammation and oxidative stress.